2013
DOI: 10.1002/hed.23219
|View full text |Cite
|
Sign up to set email alerts
|

Hypofractionated palliative radiotherapy for advanced head and neck cancer: The IHF2SQ regimen

Abstract: This regimen is an alternative to conventional chemoradiotherapy with good response rates and acceptable toxicity for selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 20 publications
1
23
0
2
Order By: Relevance
“…Other hypofractionated palliative regimens have been reported for head and neck cancers[18-22]. The “Hypo Trial” conducted by Porceddu and colleagues treated 35 incurable head and neck cancer patients with the goal of 30 Gy in 5 fractions with 2 fractions per week.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other hypofractionated palliative regimens have been reported for head and neck cancers[18-22]. The “Hypo Trial” conducted by Porceddu and colleagues treated 35 incurable head and neck cancer patients with the goal of 30 Gy in 5 fractions with 2 fractions per week.…”
Section: Discussionmentioning
confidence: 99%
“…Overall 80% of patients experienced an overall objective response with Grade 3 mucositis and dysphagia developing in 25% and 11%, respectively[22]. Monnier et al reported on a series of 78 patients treated with a concurrent hypofractionated regimen dubbed the Irradiation HypoFractionnée 2 Séances Quotidiennes (IHF2SQ) that delivered 3Gy twice daily on the first, third, fifth and seventh week of treatment with concurrent platinum-based chemotherapy with a response rate of 54% and 1% of patients developing acute Grade 3 or 4 toxicity[18]. …”
Section: Discussionmentioning
confidence: 99%
“…A retrospective review from France (Monnier et al.) analyzed patients with incurable head and neck cancer who were treated with palliative chemoradiotherapy between 1997 and 2008 using a special regimen called the IHF2SQ (Irradiation HypoFractionnée 2 Séances Quotidiennes) 5 . These patients received 3 Gy twice a day on days 1 and 3 of the week, during weeks 1, 3, 5, and 7, for a total of 48 Gy, concurrently with chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies [1619] of hypofractionated, palliative RT with a total dose of 30 to 50 Gy in 5 to 16 fractions for 2 to 5 weeks demonstrated a decent palliative response but with grade 3 acute mucositis rates as high as 18% to 66%. Another study examined the ‘‘IHF2SQ regimen (HypoFractionnée 2 Séances Quotidiennes)’’ of 3 Gy twice a day for 2 fractions, twice a week every other week for weeks 1 to 7 with concurrent, platinum-based chemotherapy for advanced head and neck cancers [20]. The reported grade 3 acute toxicity was only 4%, which is comparable to the 5% observed in our previous photon-based quad shot study with IMRT [5], whereas the median PFS was only 3.8 months [20].…”
Section: Discussionmentioning
confidence: 99%
“…Another study examined the ‘‘IHF2SQ regimen (HypoFractionnée 2 Séances Quotidiennes)’’ of 3 Gy twice a day for 2 fractions, twice a week every other week for weeks 1 to 7 with concurrent, platinum-based chemotherapy for advanced head and neck cancers [20]. The reported grade 3 acute toxicity was only 4%, which is comparable to the 5% observed in our previous photon-based quad shot study with IMRT [5], whereas the median PFS was only 3.8 months [20]. Although acute toxicity evaluation was not standardized in this study, we believe the adverse events observed are representative of patients’ palliative symptom relief.…”
Section: Discussionmentioning
confidence: 99%